It’s time to shed some light on the importance of fungi in neonatal intensive care units: what do we know about the neonatal mycobiome? - Wojciechowska, Dobrochna; Salamon, Sylwia; Wróblewska-Seniuk, Katarzyna (Frontiers in Microbiology, 2024)
The 21 st century, thanks to the development of molecular methods, including DNA barcoding, using Sanger sequencing, and DNA metabarcoding, based on next-generation sequencing (NGS), is characterized by flourishing research on the human microbiome.Microbial dysbiosis is perceived as a new pathogenetic factor for neonatal diseases. Fungi are crucial, but neglected, components of the neonatal microbiome, which, despite their low abundance, significantly impact morbidity and mortality rates of premature infants hospitalized in Neonatal Intensive Care Units (NICUs). The neonatal mycobiome's composition and effect on health remain poorly studied research areas.Our knowledge about neonatal mycobiome, composed of limited genera, is mainly based on research on the bacterial microbiome. We presume it is influenced by clinical factors, including prematurity, antibiotic therapy, and type of delivery. Understanding these risk factors may be useful in prevention strategies against dysbiosis and invasive fungal infections.Despite the methodological challenges resulting from the biology of the fungal cell, this topic is an attractive area of research that may contribute to more effective treatment, especially of newborns from risk groups. In this mini review, we discuss the current state of knowledge, research gaps, study difficulties, and future research directions on the neonatal mycobiome, concerning potential future clinical applications.